Solve the system using substitution. Write the solution as an ordered pair. (1 point) SHOW YOUR WORK FOR FULL CREDIT! (2 points)-5x + y = -1y - 4x = -3

Accepted Solution

Answer:The solution is (-2,-11)Step-by-step explanation:The given system is [tex]-5x+y=-1[/tex]and[tex]y-4x=-3[/tex]Make y the subject in the first equation to get;[tex]y=5x-1[/tex]Put [tex]y=5x-1[/tex] into the second equation.[tex]5x-1-4x=-3[/tex]Group similar terms;[tex]5x-4x=-3+1[/tex][tex]x=-2[/tex]Put [tex]x=-2[/tex] into [tex]y=5x-1[/tex].This implies that;[tex]y=5(-2)-1[/tex][tex]y=-10-1[/tex][tex]y=-11[/tex]The solution is (-2,-11)